Recent Advances in Modeling and Simulation Tools for Communication Networks and Services - Ince, Nejat; Bragg, Arnold (Springer US : Imprint: Springer, 2007)
This book contains a selection of papers presented at a Symposium organized under the aegis of COST Telecommunications Action 285. The main objective of the Action is to enhance existing modeling and simulation tools and to develop new tools for research in emerging multi-service telecommuncation networks in the areas of model performance improvement, multilayer traffic modeling, and the important issue of evaluation and validation of the new modeling tools. The studies related to the activities above are carried out by members of the Action Group with contributions from invited experts/scientists from non-COST countries, academia and industry (within and outside Europe). The book is a collection of important aspects of study results achieved by this distinguished group of experts/scientists from Europe and the US. The book is divided into the following six areas: - Multilayer Modeling - Wireless and Sensor Networks - Verification and Validation - High Throughput Systems - Traffic - Applications of Simulation A useful reference work for academic researchers and practitioners, this book is the third in a series of works focusing on modeling and simulation methods, techniques, and tools in telecommunications. Previous works in this series are: Modeling and Simulation Tools for Emerging Telecommunications Networks: Needs, Trends, Challenges and Solutions, by A. Nejat Ince and Ercan Topuz (editors), Springer, 2006, 510 pages, ISBN: 978-0-387-32921-5 Modeling and Simulation Environment for Satellite and Terrestrial Communications Networks, by A. Nejat Ince (Editor), Springer, 2004, 424 pages, ISBN: 978-0-7923-7547-0.